Insecurity orientations: A person-centered approach to existential concerns. (1st January 2021) - Young, Isaac F.; Sullivan, Daniel; Hart, Joshua; Palitsky, Roman
Abstract: This research explores the ways in which psychological insecurities in three domains—the self, meaning, and relationships—are distributed intra-individually. Specifically, we explore the hypothesis that certain profiles of insecurity are associated with sociocultural and personality indicators. Building upon recent theorizing regarding psychological security (Hart, 2014) and cultural-existential psychology (Sullivan, 2016), two studies ( N = 1049) support the existence of hypothesized "insecurity orientations." Insecurities tended to distribute intra-individually in accordance with three insecurity prototypes: Social Concern (relatively concerned with relationships and unconcerned with meaning), Meaning Concern (relatively concerned with meaning and unconcerned with relationships), and Secure (relatively secure in all resources). Using the resultant cluster solutions as a foundation, theorized differences in sociocultural (e.g., religiosity, political orientation, individualism-collectivism) and personality indicators (e.g., attachment and the Big Five) are investigated. Results support the hypothesized relationships between insecurity orientations and sociocultural and personality variables (e.g., meaning-concerned individuals are less religious than socially-concerned individuals). Implications for global wellbeing are then considered, including the possibility that insecurity orientations may leave individuals more vulnerable to some types of distress than others (e.g., anxiety vs. depression).